Kinematics and the Implementation of a Modular Caterpillar Robot in Trapezoidal Wave Locomotion. (1st August 2013) - Wei, Hongxing; Cui, Yuanyang; Li, Haiyuan; Tan, Jindong; Guan, Yong; Li, Yong-Dong
With the development of bionic engineering, research into bionic robots has become a popular topic. In this field, the design of robotic mechanisms to realize the locomotion of insects forms a significant research branch. The current paper presents a caterpillar robotic mechanism that is composed of our newly-developed self-assembly modular robots (Sambot). A trapezoidal wave locomotion gait is planned for the caterpillar mechanism and the kinematics equations are established and solved analytically for such locomotion. The variations of the kinematics quantities are illustrated and discussed. The variation of the jump of the angular acceleration indicates that it is better to apply the trapezoidal wave gait to low velocity situations. Finally, the obtained data of the kinematics quantities is used to perform the gait control locomotion experiment and the errors of the experimental data are analysed in depth.